2015
DOI: 10.3389/fpsyg.2015.00581
|View full text |Cite
|
Sign up to set email alerts
|

Shape and spatial working memory capacities are mostly independent

Abstract: Whether visual working memory (WM) consists of a common storage resource or of multiple subsystems has been a controversial issue. Logie (1995) suggested that it can be divided into visual (for color, shape, objects, etc.) and spatial WM (for location). However, a recent study reported evidence against this hypothesis. Using a dual task paradigm, Wood (2011) showed interference between shape and spatial WM capacities, suggesting that they share a common resource limitation. We re-examined this finding controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…A dual-task paradigm is often used to examine the interaction between two distinct mental mechanisms, such as the interaction between attention and WM (e.g., Woodman et al, 2001; Xin & Li, 2020), and the interaction between spatial WM and visual WM (e.g., Sanada et al, 2015; Wood, 2011). However, because attention is involved in the maintenance of WM (Barrouillet et al, 2011; Cowan, 2005), when dual-task cost in capacity is observed in a WM task it is often difficult to tell whether the dual-task cost is due to interference from executive processes or from nonexecutive processes (such as interference across WM representations).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A dual-task paradigm is often used to examine the interaction between two distinct mental mechanisms, such as the interaction between attention and WM (e.g., Woodman et al, 2001; Xin & Li, 2020), and the interaction between spatial WM and visual WM (e.g., Sanada et al, 2015; Wood, 2011). However, because attention is involved in the maintenance of WM (Barrouillet et al, 2011; Cowan, 2005), when dual-task cost in capacity is observed in a WM task it is often difficult to tell whether the dual-task cost is due to interference from executive processes or from nonexecutive processes (such as interference across WM representations).…”
Section: Discussionmentioning
confidence: 99%
“…This issue affects at least two types of studies when using the dual-task paradigm. One is to study whether different stimuli (e.g., spatial vs. visual) depend on a common representation substrate (Sanada et al, 2015; Wood, 2011). The other is to explore whether information presented in a nonmemory task (e.g., target detection) is stored in WM (Oberauer & Kliegl, 2006; Oberauer et al, 2012).…”
mentioning
confidence: 99%
“…In other words, mixed-category trials spread the WM load across a larger pool of neurons compared to uniform-category trials. Our inspiration was to follow up on work demonstrating a mixed-category benefit in a large group of behavioral participants and associating it with more distinct neural patterns in a separate, smaller group of fMRI participants (Cohen et al, 2014), and work revealing detectible classification differences in category-selective regions during WM tasks (Han et al, 2013; Johnson & Johnson, 2014; Sanada et al, 2015). What we observed was more complex and nuanced, as is often the case.…”
Section: Discussionmentioning
confidence: 99%
“…It follows that WM trials distributing neural activity across different category-specific regions might support WM performance better than when the stimuli fall within the same category. Support for this view comes from a recent paper showing little interference in WM when the stimuli were visual shapes and visuospatial stimuli believed to have distinct neural representations (Sanada, Ikeda, & Hasegawa, 2015).…”
mentioning
confidence: 99%
“…Based on the multicomponent workspace of working memory in working memory theory [12], working memory has temporary limited-capacity memory systems for verbal (articulatory loop) and non-verbal (visuospatial scratchpad) material that connects with the content from long-term memory. However, according to the research conducted by Sanada [13] in 2015, shape and spatial workingmemory capacities are mostly independent. Therefore, we needed to test whether visual and spatial channels in the cognition stage should be separated as well.…”
Section: Revising Wicken's Multiple Resource Theorymentioning
confidence: 99%